Feasibility Analysis of the Development of STEM-Based Physics E-Book with Self-Regulated Learning on Global Warming Topics - Lestari, Dwi Ayu; Suwarma, I. R.; Suhendi, Endi (Indonesian Journal of Teaching in Science, 2024)
This study aims to analyze the feasibility of a physics e-book based on STEM with self-regulated learning on global warming topics. This research is a design-based research (DBR) using 4D models (define, design, develop, and disseminate). The research sample refers to 3 expert assessments consisting of 2 expert lecturers and 1 senior high school physics teacher. Then the responses of 36 students. The instrument used is an expert validation sheet and legibility tests of the main idea of the e-book on each page. The results of data analysis using Aiken validation show that: 1) the suitability of the material with STEM is 0.83 in the category of valid, 2) the suitability of the e-book with Self-regulated learning (SRL) is 0.78 in the category of valid, and 3) the feasibility of e-book is 0.82 in the category of valid. Meanwhile, the results of the readability test showed a proportion of 99.83% in the good category. So, the development of a physics e-book base on STEM with self-regulated learning on global warming topic is "feasible" to be widely implemented